The Concepts of Normativity and Descriptivism in the Work of Abdelrahman Hadj Salah - nour, fatima-ezzahra; laouidji, ahmed (El Omda in Linguistics and Discourse Analysis, 2025)
Since the appearance of the modern language science, dualities and terms based on correspondence appeared in order to study the language, how to study it, and the correct way of studying it. Thus, the modern language science- the structuralist- preferred the term “descriptivism” as a substitute to the traditional term “standardness” that was used to study and extrapolate the linguistic rules. Because the Arab grammar was criticized in the modern era and indicted of being standardized, the Algerian researcher tried to stop at the limits of this standard and discuss its bases and the extent of employment of these conditions in the Arab grammar. Based on what has been said, we raise the following problematic: What is standardness and what are its characteristics? What is descriptiveness and what are its characteristics? How was the Arab grammar criticized as being standardized? How did Abdurrahman al Hadj Saleh discuss the question of the standardness of the Arab grammar?